Prediction of carcass energy content of Pelibuey ewes by ultrasound measurements - Rodríguez-Valenzuela, Enmanuel; Chay-Canul, Alfonso J.; Salazar-Caytun, Rosario; Herrera, Ricardo Alfonso Garcia; Piñeiro-Vázquez, Angel T.; Casanova-Lugo, Fernando; Velázquez-Martínez, José R.; Herrera-Camacho, José (Ecosistemas y Recursos Agropecuarios, 2017)
The aim of this study was to evaluate the relationship between body ultrasound measurements (USM) and carcass energy content (CEC) of Pelibuey ewes. USM were taken 24 h before slaughter in twenty-two ewes. Fat thickness (FT) and Longissimus dorsi area (LDA) were determined in the thoracic (TFT and TLDA) and lumbar region (LFT and LLDA). CEC was considered as the sum of the energy of muscle and adipose tissues in the carcass. The correlation coe cient (r) between body weight (BW) and CEC was 0.89 (p < 0.001). Nonetheless, correlations for LDA and CEC were not signi cant (p > 0.05). The r2 for equation including BW and LFT was 0.87 (RSD= 15.34). The inclusion of LFT improved the prediction by about 8 %. The use of some USM in combination with BW provides good CEC estimates in Pelibuey ewes.
Keywords: Body condition; ultrasound; carcass energy.